Pengaruh Stres Kerja dan Kepuasan Kerja Terhadap Turnover Intention Karyawan di Kota Batam - Nanda Harry Mardika; Argo Putra Prima (LPPM Universitas Putera Batam, 2020)
This study aims to examine the variables that influence employee turnover intention in Batam City. The purpose of this study is to determine the effect of job stress and job satisfaction toward employee turnover intention partially and simultaneously. Total of Samples are 96 respondents which were taken by using purposive sampling method and then the data was analyzed by SPSS Program. Methodology in this research is descriptive with a quantitative approach. This study shows that job stress partially has positive and significant effect on employee turnover intention with t value 3.532 and significant value 0,001. Job satisfaction partially has negative and significant effect on employee turnover intention with t value -2.509 and significant value 0,014. Simultaneously, this Research shows that job stress and job satisfaction have positive and significant effect on employee turnover intention with t value 13.213 and significant value 0,000.